Analisis terhadap Ahli Waris Laki-Laki dan Konsep Penyelesaian Bagiannya dalam Kajian Alqur’an dan Hadis - Raja Ritonga; Zuhdi HSB; Khairul Bahri Nasution (Pascasarjana IAIN Sultan Amai Gorontalo, 2024)
The transfer of inheritance is closely related to the heir and the heir. An heir must have a relationship or bond with the heir. The sex of an heir influences the determination of the portion they will receive. The Qur'an and Hadith have clearly described and mentioned each heir and their respective parts. Therefore, the number of male heirs is more mentioned as recipients of inheritance. So, this study aims to analyze male heirs and the concept of completing their share in the study of the Qur'an and Hadith. The research method used is a qualitative method with a type of library research. In collecting the required data, the researcher searched for various books, articles, and other scientific works related to the research theme. Furthermore, the found data were analyzed descriptively with a conceptual and interpretation approach. The conclusion in this study is that male heirs are categorized into four categories: (1) heirs who inherit as ashabul furudh only. (2) heirs who receive the inheritance as ashobah only. (3) heirs who inherit as ashabul furudh and ashobah at the same time. (4) the heirs who get the inheritance are sometimes as ashabul furudh and sometimes as ashobah.